The Influence of E-Samsat Implementation, Taxpayer Awareness, and Income Levels on Compliance with Motor Vehicle Tax Payments - Suryadi, Arief; Rahmat, Nur; PurboJati, Nurrakhman; Sunarsih, Uun; Mais, Rimi Gusliana (Journal of Accounting, Management, and Economics Research (JAMER), 2025)
This study uses quantitative methods to investigate the effects of the implementation of the e-samsat system, tax awareness, and income rates on compliance with motor vehicle tax payments. Data yang digunakan adalah data utama by distributing the questionnaire to taxpayers registered in the eastern Jakarta territory and sampling techniques using pursposive samplings and obtained 50 respondents. Pre-conditional analysis tests using validity tests, reliability tests, normality tests, multicolinearity trials, heterocadastisity tests dengan menggunakan spss 25, kemudian melakukan analisis regresi linier dan tes parsial (uji t). Hasil penelitian menunjukkan bahwa penerapan e-samsat tidak mempengaruhi kepatuhan terhadap pembayaran pajak karena masih ada beberapa who have not accepted socialization against e-Samsat. The variable of tax awareness has an influence on compliance with tax payments because with consciousness then the taxpayer is involved in supporting the development process, and the variable rate of income has no influence over the compliance of tax payment.